Museologia e Moda : a documentação museológica do acervo documental referente aos desfiles do estilista paraense André Lima no São Paulo Fashion Week - CONCEIÇÃO, Bernardo Baia dos Santos (2019)
Museological documentation is one of the activities of musealization of collections, a process that involves preventive conservation, communication and research, which permeates all museological functions. The museological research for the development of the actions of documentation of collections allows the investigation of information intrinsic and extrinsic to the objects in order to expand the knowledge about a certain scope of analysis. In this way, the research started from an informational demand of the cataloging sheet called the field of related objects, with the premise that the collection donated to the Universidade Federal do Pará, which goes through musealization processes through the University Extension Project Curadoria de Acervos na Seção Moda da Coleção Amazoniana de Arte, expands the knowledge about the professional trajectory of the brazilian fashion designer André Lima by the identification of the documents and objects related to the parades in São Paulo Fashion Week. The aim of this study was to investigate the informative potential of the documentary collection of clippings with magazines and newspapers reports referring to the first five paredes of the fashion designer at the São Paulo Fashion Week to subsidize the museological documentation of the other categories of the collections; To conceive the models of the museological documentation for the documentary collection of clipping; And to contextualize the information of the documentary collection of clipping along the identification of the categories of collection of clothes, accessories and fixtures related to the parades. Therefore, the research of collections for the museological documentation allowed the identification and registration of the objects that were launched in the parades and a knowledge about a part of the professional trajectory of André Lima for researches in the field of museology and fashion.